Nominalization as a Feature of Functional Morpho-Syntactic Complexity in EFL Medical Scholarly Research Writing - HASSAN BOUKHRIS; SANA SAKALE (Journal of English Language Teaching and Applied Linguistics, 2025)
Academic communication being mainly in the written mode has given primacy to EFL learners’ writing skills development. Although academic writing is, on the whole, characterized by formality, conciseness, and clarity, specialized writing within this genre reflects further specificities, the awareness and mastery of which is an index of genre proficiency. This study explores nominalization as a means of information packing and linguistic complexity used in the medical scholarly research writing for complex meaning-making. The study was carried out on the premise of Systemic Functional Linguistics (SFL) that language is a network of systems and serves functions, and that it offers a repertoire of choice for meaning-making, strategically deployed in context. Accordingly, nominalizations through suffixation were identified in 80 research articles Discussion sections written by Moroccan medical researchers, using a computational tool. Nominalization patterns were analyzed, and nominalizations’ functional affordances in these specialized academic discourse texts were counted and categorized. Results show an over-reliance on nominalized scientific information post-modification through prepositional phrases and pre-modification through attribute adjectives and nouns, respectively. Other nominalization affordances were found to be underused. These findings provide evidence for the effectiveness of the SFL outlook in fully exploiting the language meaning-making potential and raising awareness of valued functional use of linguistic devices in academic discourse. Functional grammar instruction, incorporation of genre pedagogy, and instruction of conventionalized functional linguistic complexity such as nominalization would benefit academic writing development and specialized scientific register proficiency advancement.